The Mineral Composition of Milk from High-Yielding Dairy Cows Depending on the Month of Lactation and Udder Health - Anna Nogalska; Martyna Momot; Zenon Nogalski (Applied Sciences, 2020)
The aim of this study was to determine the effects of the month of lactation and udder health of high-yielding Polish Holstein-Friesian (PHF) cows on daily milk production and the content of K, Ca, Na, Mg and Zn in milk. The experimental materials comprised 380 milk samples collected from 38 cows. The highest average daily milk yield (49.1 kg) was noted in cows in the second month of lactation and, considering udder health, in cows whose milk contained 201,000 to 400,000 somatic cells per mL on average (denoting risk of mastitis). The K content of milk increased (p < 0.05) in successive months of lactation, whereas the opposite trend was observed in the Zn content of milk. The average content of Ca (842 mg∙dm−3), Na (344.5 mg dm−3) and Mg (98.5 mg dm−3) in milk was below the lower limits of the normal physiological ranges. Milk from cows with healthy udders (≤200,000 somatic cells per mL) had the highest concentration of K, whereas the levels of Na and Zn were highest in milk from cows with clinical mastitis (> 1 mln somatic cells per mL). Udder inflammation was accompanied by an increase in the levels of Na and Zn in milk. The high content of Na and Zn in milk can be an additional indicator of mastitis in cows.